Seuss celebration : 9 favorite televised classics. - Seuss, Dr; Sherman, Allan, 1924-1973; Butler, Daws; Adams, Mason; Holt, Bob, 1928-1985; Albert, Eddie; Conried, Hans; Smith, Hal, 1916-1994 (Franchise collection., 2005)
The cat in the hat: Two youngsters find themselves bored at home, but when the mischievous Cat in the Hat arrives, they're cat-apulted into a day of rousing, romping antis.